Augmented Reality Technology as a Complement on Graphic Design to Face Revolution Industry 4.0 Learning and Competence: The Development and Validity - Huda, Asrul; Azhar, Nelda; Almasri, Almasri; Wulansari, Rizky Ema; Mubai, Akrimullah; Sakti, Rizki Hardian; Firdaus, Firdaus; Hartanto, Suryo (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study aims at developing the augmented reality application technology, a complementary learning on graphic design to face the skills and learning of the industrial revolution 4.0. This study uses a 4D (four-D) development method for the development of augmented reality application technology and uses a survey method for validity. This AR application will be validated by 12 experts, while the respondents used in filling out the needs analysis questionnaire at the define stage (four-D) are students and lecturers of Informatics Engineering Education, Padang State University. The results of this study indicate that on the analysis of the achievement of the learning process, it can be seen that there are still expectations and advantages in the achievement of the learning process desired by lecturers and students, where the learning process is still in the sufficient category and 80%, students need development of technology as complement reality to be used as learning media in the learning process. The validation test also shows that the augmented reality application technology is included in the valid category with an average value of V value of 0.933. So, it cannot be denied that the augmented reality application technology is valid to be used in the learning process.